PENDALAMAN MATERI AKUNTANSI DASAR BAGI SISWA/I SMA TARSISIUS I - Wijoyo, Amin; Esperansya Desmonda Woen; Nathaniel Edbert Lioe (Jurnal Serina Abdimas, 2024)
The rapid development of technology makes mastering basic accounting knowledge crucial for accountants. The community service program at SMA Tarsisius I aims to improve students' understanding of basic accounting concepts, particularly in relation to posting journal entries into ledgers, which is a vital foundation for those who wish to pursue higher-level accounting studies. Additionally, SMA Tarsisius I faces challenges in delivering a large amount of material within a limited time, causing the focus of teaching to shift from student understanding to merely completing the entire curriculum. Therefore, education for students at SMA Tarsisius I in the form of community service was conducted by lecturers and students from Tarumanagara University, with the hope of contributing to the advancement of Indonesia's education ecosystem. The activity was held offline on September 11, 2024, and was attended by 10 students from SMA Tarsisius 1. The teacher will conduct interactive learning activities, including pre-tests, concept and theory presentations, practice question discussions, and post-tests. The results of the activity show an increase in students' understanding from 50% to 100%, as shown by the quiz results. These results indicate that the learning activities provided have successfully improved students' understanding of ledgers. As a follow-up, teachers and school authorities can conduct further activities to monitor students' progress in applying basic accounting concepts. ABSTRAK Perkembangan teknologi yang semakin pesat membuat penguasaan ilmu akuntansi dasar menjadi sangat penting bagi para akuntan. Program pengabdian kepada masyarakat di SMA Tarsisius I bertujuan untuk meningkatkan pemahaman siswa/i terhadap konsep akuntansi dasar, terutama terkait posting jurnal ke dalam buku besar, yang menjadi fondasi penting bagi mereka yang ingin melanjutkan studi akuntansi di jenjang yang lebih tinggi. Selain itu, SMA Tarsisius I menghadapi tantangan dalam menyampaikan materi yang banyak dengan waktu yang terbatas, sehingga fokus pengajaran sering beralih dari pemahaman siswa menjadi sekadar menyelesaikan seluruh kurikulum. Untuk itu, edukasi untuk siswa/i di SMA Tarsisius I dalam bentuk PKM diadakan oleh dosen dan mahasiswa/i Universitas Tarumanagara dengan harapan dapat berkontribusi bagi kemajuan ekosistem pendidikan di Indonesia. Kegiatan dilaksanakan secara luring pada tanggal 11 September 2024 dan diikuti oleh 10 siswa-siswi SMA Tarsisius 1. Pengajar akan mengadakan kegiatan pembelajaran yang interaktif, meliputi pre-test, pemaparan konsep dan teori, pembahasan latihan soal, dan post-test. Hasil kegiatan menunjukkan peningkatan pemahaman siswa/i dari 50% menjadi 100% yang ditunjukkan melalui hasil kuis. Hasil tersebut mengindikasikan bahwa kegiatan pembelajaran yang diberikan telah berhasil meningkatkan pemahaman siswa/i tentang buku besar. Sebagai tindak lanjut, pengajar maupun pihak sekolah dapat mengadakan kegiatan lanjutan untuk memantau kemajuan siswa/i dalam mengaplikasikan konsep akuntansi dasar.